The effect of buparvaquone treatment on the levels of some antioxidant vitamins, lipid peroxidation and glutathione peroxidase in cattle with theileriosis - Naziroglu, M; Saki, CE; Sevgili, M (Wiley, 1999)
Plasma levels of vitamins A, E, beta carotene, both plasma and erythrocyte glutathione peroxidase (GSHPx), lipid peroxidation (LPO) and reduced glutathione (GSH) were investigated in cattle naturally infected with Theileria annulata and treated with buparvaquone. There were two groups each containing 30 cattle. Naturally infected cattle were used in the second group. Buparvaquone (2.5 mg/kg body weight) was administered to animals in the second group. Blood samples were taken from control animals, and immediately before treatment, and from animals 10 days after the injection of buparvaquone. Detection of the infected animals was carried out by blood smears. Plasma vitamins A, E, beta carotene, both plasma and erythrocyte GSHPx, LPO and GSH levels were determined. The levels of LPO in plasma and erythrocyte samples were significantly (P < 0.05, P < 0.01) higher after treatment than in either control animals or before treatment. Plasma levels of antioxidant vitamins, vitamin E and beta carotene were significantly (P < 0.05, P < 0.01) lower after treatment than in either control animals or before treatment, while the vitamin E level was found to be higher before treatment than in either the control group or animals after treatment (P < 0.05, I) < 0.01). The levels of vitamin A in plasma and the activity of GSHPx and GSH in both plasma and erythrocytes in control animals after and before treatment did not differ significantly. In conclusion, we observed that there was a decreased plasma level of vitamin E and beta carotene and an increased level of LPO in cattle treated with buparvaquone. Buparvaquone might function in the treatment of Theileria annulata by forming free radicals.
Keywords: Selenium; Erythrocytes; Qinghaosu; Liver; Mice; Combination; Falciparum; Parasites; Invitro; Damage